Textures of the ordinary : doing anthropology after Wittgenstein - Das, Veena (Thinking from elsewhere., 2020)
Textures of the Ordinary shows how anthropology finds a companionship with philosophy in the exploration of everyday life. Based on two decades of ethnographic work among low-income urban families in India, Das shows how the notion of texture aligns ethnography with the anthropological tone in Wittgenstein and Cavell, as well as in literary texts. The book shows different routes of return to the everyday as it is corroded not only by catastrophic events but also by repetitive and routine violence within everyday life itself. As an alternative to normative ethics, this book develops ordinary ethics as attentiveness to the other and as the ability of small acts of care to stand up to horrific violence. Textures of the Ordinary offers a model of thinking in which concepts and experience are shown to be mutually vulnerable. The book is an intellectually intimate invitation into the ordinary, that which is most simple yet most difficult to perceive in our lives.